2016
DOI: 10.1016/j.molp.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis WRKY Transcription Factors WRKY12 and WRKY13 Oppositely Regulate Flowering under Short-Day Conditions

Abstract: In plants, photoperiod is an important cue for determining flowering. The floral transition in Arabidopsis thaliana is earlier under long-day (LD) than under short-day (SD) conditions. Flowering of Arabidopsis plants under SD conditions is mainly regulated by the plant hormone gibberellin (GA). Here, we report two WRKY transcription factors function oppositely in controlling flowering time under SD conditions. Phenotypic analysis showed that disruption of WRKY12 caused a delay in flowering, while loss of WRKY1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(154 citation statements)
references
References 51 publications
9
145
0
Order By: Relevance
“…WRKYs are TFs that have been reported to induce dwarfing (Cai et al, 2014;Guo et al, 2015;Li et al, 2016). We screened five dwarfing rootstocks and five nondwarfing rootstocks of apple and detected the expression of 29 WRKY genes that may function in plant development.…”
Section: Researchmentioning
confidence: 99%
“…WRKYs are TFs that have been reported to induce dwarfing (Cai et al, 2014;Guo et al, 2015;Li et al, 2016). We screened five dwarfing rootstocks and five nondwarfing rootstocks of apple and detected the expression of 29 WRKY genes that may function in plant development.…”
Section: Researchmentioning
confidence: 99%
“…So far, 70 WRKY proteins in Arabidopsis and > 100 in rice have been found (Wu et al, 2005;Ross et al, 2007). WRKY TFs have been reported to play multifaceted roles in plant growth and development (Eulgem et al, 2000;Rushton et al, 2010), including biotic and abiotic stress responses (Jiang J. et al, 2017), leaf senescence (Jiang et al, 2014;Chen et al, 2017), anthocyanin and proanthocyanidin biosynthesis (Devaiah et al, 2007;Gonzalez et al, 2016;Verweij et al, 2016;Duan et al, 2018), flowering (Li et al, 2016), seed development (Zhang et al, 2011;Ding et al, 2014) and trichome patterning (Pesch et al, 2014). In particular, the WRKY proteins TTG2 and PH3 affect flavonoid biosynthesis by interacting with the WBM complex in Arabidopsis and Petunia, respectively (Gonzalez et al, 2016;Verweij et al, 2016;Lloyd et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the first comprehensive review of the WRKY protein, SPF1 was reported to have been cloned from sweet potato 22 years ago. Since then, many WRKY genes have been found in multiple species, including Arabidopsis , rice, wheat, and soybean (Ishiguro and Nakamura, 1994; Ren et al, 2010; Wang F. et al, 2015; Wang et al, 2016; He Y. et al, 2016; Li W. et al, 2016; Yang et al, 2016). PlantTFDB (V4.0) contains 14,549 WRKY genes from 166 species.…”
Section: Introductionmentioning
confidence: 99%